PERANAN KOMUNITAS FEMINIS DALAM PEMBERDAYAAN PEREMPUAN DI KOTA MEDAN (STUDI KASUS: KOMUNITAS PEREMPUAN HARI INI) - Simanjuntak, Felix; Suriadi, Agus (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2022)
Women are a very vulnerable group in our society. Women are very vulnerable to sexual violence, social injustice due to the concept of gender in a society that does not have equality. Women have struggled for a long time and made various progress in every wave of their struggle. In fact, today's women's struggle has entered the fourth phase or wave, where the struggle is focused on sexual and economic violence. Even so, each region has its own root cause, in order to build universal feminism values, every group, organization or feminist community must adjust the pattern of movement so that the services and empowerment they carry out do not seriously confront the values ​​and norms of the local community. With this awareness, the women's community is present as a symbol and lighter for women's resistance and empowerment in the city of Medan. The purpose of this study was to analyze and find out in depth in order to gain new insights about the role of the Women's Feminist Community Today in empowering women in the city of Medan. Informants in this study were divided into three groups, namely key informants, namely the founders of the Perempuan Hari Ini community, the main informants were internal members of the Perempuan Hari Ini community and additional informants were feminist activists who are not internal members of the community but are often involved in activities carried out by Women Today. . Data collection techniques were carried out by literature study, observation, interviews and documentation. The data obtained were then processed qualitatively to obtain conclusions from the research. The results of the research concluded that the Today's Women's Community has a very significant role in empowering women in the city of Medan, especially for its internal members. In addition, this community has also become a symbol and a lighter to fight for gender equality so that women are more empowered.